(untitled) (Baghdad Science Journal, 2020)
Rice (Oryza sativa) is a fundamental food for the majority of world population. Cyclin Dependent Kinase -A (CDKA) accelerates transition through different stages of cell cycle and contributes in gametes formation. In the present investigation, a CDKA encoding gene along with the corresponding protein were characterized in O. sativa Indica Group, O. glaberrima, O. barthii, O. brachyantha, O. glumipatula, O. longistaminata, O. meridionalis, O. nivara, O. punctata and O. rufipogon using in silico analyses. The results reflected little variation in most species except O. longistaminata and O. brachyantha. Compared with the remaining species, O. longistaminata lacked a negative regulatory binding site and had a modified cyclin binding site (PSTAICE instead of PSTAIRE) that may lead to future characterization of a new distinct subclass of CDKAs. O. brachyantha had a modified SUC/CKS (suppressor of CDC2/cyclin dependent-kinase regulatory subunit)-binding motif. The observed variations can be exploited through traditional breeding or molecular approaches to manipulate cell division and growth of cultivated Oryza species.